DUXAIT-NG in Practice: Evaluating Usability on the Municipality of Lima Website - (:unkn) unknown (Springer Nature Switzerland, 2024)
Within the framework of a workshop held to present the DUXAIT-NG platform, a heuristic evaluation with the approach proposed by Granollers was carried out as a case study, with the participation of 20 participants with different profiles and experience i...
Keywords: Usabilidad web; Municipalidad de Lima